2018
DOI: 10.1038/s41598-018-30548-w
|View full text |Cite
|
Sign up to set email alerts
|

Room temperature processed high mobility W-doped In2O3 electrodes coated via in-line arc plasma ion plating for flexible OLEDs and quantum dots LEDs

Abstract: We fabricated W-doped In2O3 (IWO) films at room temperature on a flexible PET substrate using an in-line arc plasma ion plating system for application as flexible transparent conducting electrodes (FTCEs) in flexible organic light emitting diodes (OLEDs) and quantum dots light emitting diodes (QDLEDs). Due to the high-energy flux of the sublimated ions generated from the plasma region, the IWO films showed a well-developed crystalline structure with a low sheet resistance of 36.39 Ohm/square and an optical tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…However, quite a limited amount of research attention is paid to the study of the resistance response of the electrically conductive thin films to both compression and tension during the bending. Up to date, most of such studies were devoted to the durability of silver paint electrodes deposited on polymer substrates for wearable electronics [ 14 , 15 ], silver networks covered by polymer for flexible thin film heaters [ 16 ], and flexible metal oxide electrodes on polymer substrates for touch-screen panels [ 17 ] and flexible OLED applications [ 18 ]. In most of these works, the resistance measurements were applied to determine the limits for mechanical bending and durability.…”
Section: Introductionmentioning
confidence: 99%
“…However, quite a limited amount of research attention is paid to the study of the resistance response of the electrically conductive thin films to both compression and tension during the bending. Up to date, most of such studies were devoted to the durability of silver paint electrodes deposited on polymer substrates for wearable electronics [ 14 , 15 ], silver networks covered by polymer for flexible thin film heaters [ 16 ], and flexible metal oxide electrodes on polymer substrates for touch-screen panels [ 17 ] and flexible OLED applications [ 18 ]. In most of these works, the resistance measurements were applied to determine the limits for mechanical bending and durability.…”
Section: Introductionmentioning
confidence: 99%
“…As ITO is brittle, it may not be efficient in applications involving many bending cycles or high curvature folding. Indeed, it was shown that ITO substrates have their electrical properties conserved for bending with radii higher than 10 mm . However, in the case of photodynamical therapy, one application that we are thinking, bending is gentle (body curvatures have radii far higher than 10 mm), and also, the number of bending cycles is small.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, it was shown that ITO substrates have their electrical properties conserved for bending with radii higher than 10 mm. 82 However, in the case of photodynamical therapy, one application that we are thinking, bending is gentle (body curvatures have radii far higher than 10 mm), and also, the number of bending cycles is small. Also, the onion substrate can be used as a basis for other conductive thin films that support many bending cycles.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The application of a transparent conducting layer (TCL) dates back to 1902 when CdO was discovered as the first TCL material . Currently, the energy gap of TCL materials, such as indium tin oxide (ITO), zinc oxide, indium oxide (In 2 O 3 ), and tin oxide (SnO 2 ), must be greater than that of materials with a band gap of 3 eV to achieve a high visible light transmittance. ITO has recently become the predominant transparent conductive film in LED applications. , ITO comprises 90% In 2 O 3 and 10% SnO 2 .…”
Section: Introductionmentioning
confidence: 99%